Effect of yttrium addition on flow behavior of Cu-Zr-Al bulk metallic glass in the supercooled liquid region - 杨珂 范新会 李炳 李艳红 王鑫 徐璇璇 (Journal of rare earths, 2017)
The high temperature deformation behaviors and thermal workability of Cu43Zr48Al9 and(Cu43Zr48Al9)98Y2 bulk metallic glasses in the supercooled liquid region were investigated by the uniaxial compression tests. The results showed that the high temperature deformation behaviors were highly sensitive to strain rate and temperature, and the flow stress decreased with the increase of temperature, as well as with the decrease of strain rate. Additionally, the(Cu43Zr48Al9)98Y2 bulk metallic glass displayed smaller flow stress under the same condition. The flow behavior changed from Newtonian to non-Newtonian with increase of the strain rate, as well as the decrease of temperature, which could be explained by the transition state theory. We found that(Cu43Zr48Al9)98Y2 bulk metallic glass had better flow behavior than the Cu43Zr48Al9 bulk metallic glass in the supercooled liquid region. In addition, the processing maps of the two bulk metallic glasses were constructed considering the power dissipation efficiency. The optimum domain for thermal workability of the bulk metallic glass was located using the processing map, where the power dissipation efficiency was larger than 0.8. It was shown that the(Cu43Zr48Al9)98Y2 bulk metallic glass, which had larger area of optimum domain, had excellent thermoplastic forming.